2022
DOI: 10.1007/s11030-022-10405-9
|View full text |Cite
|
Sign up to set email alerts
|

Defective ORF8 dimerization in SARS-CoV-2 delta variant leads to a better adaptive immune response due to abrogation of ORF8-MHC1 interaction

Abstract: In India, during the second wave of the COVID-19 pandemic, the breakthrough infections were mainly caused by the SARS-COV-2 delta variant (B.1.617.2). It was reported that, among majority of the infections due to the delta variant, only 9.8% percent cases required hospitalization, whereas only 0.4% fatality was observed. Sudden dropdown in COVID-19 infections cases were observed within a short timeframe, suggesting better host adaptation with evolved delta variant. Downregulation of host immune response agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…16,[25][26][27] Recently, the role of ORF8 has been particularly pointed out. [28][29][30] Indeed, this small water-soluble immunoglobulin-(Ig)-like protein is interfering with the immune system response, particularly by interacting with monocytes. 31 The structure of ORF8 in bat and human coronaviruses has also been resolved, and the molecular bases of its perturbation of the immune response, which proceeds through the formation of sulphurbridge mediated large scale aggregates, has been discussed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,[25][26][27] Recently, the role of ORF8 has been particularly pointed out. [28][29][30] Indeed, this small water-soluble immunoglobulin-(Ig)-like protein is interfering with the immune system response, particularly by interacting with monocytes. 31 The structure of ORF8 in bat and human coronaviruses has also been resolved, and the molecular bases of its perturbation of the immune response, which proceeds through the formation of sulphurbridge mediated large scale aggregates, has been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…31 The structure of ORF8 in bat and human coronaviruses has also been resolved, and the molecular bases of its perturbation of the immune response, which proceeds through the formation of sulphurbridge mediated large scale aggregates, has been discussed. 30,32 However, the importance of ORF8 goes way beyond this direct Ig-like effect. More recently, it has been shown that ORF8 is able to penetrate the nuclear membrane and accumulates in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The structure of ORF8 in bat and human coronaviruses has also been resolved, and the molecular bases of its perturbation of the immune response, which proceeds through the formation of sulfurbridge mediated large scale aggregates, have been discussed. 34 However, the importance of ORF8 goes way beyond this direct Ig-like effect. More recently, it has been shown that ORF8 is able to penetrate the nuclear membrane and accumulates in the nucleus.…”
mentioning
confidence: 99%
“… 35 The structure of ORF8 in bat and human coronaviruses has also been resolved, and the molecular bases of its perturbation of the immune response, which proceeds through the formation of sulfur-bridge mediated large scale aggregates, have been discussed. 34 , 36 …”
mentioning
confidence: 99%